2017
DOI: 10.3892/etm.2017.5559
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑30a suppresses non‑small‑cell lung cancer by targeting Myb‑related protein B

Abstract: Abstract. Non-small-cell lung cancer (NSCLC) is one of the leading causes of cancer mortality worldwide. A growing body of evidence indicates that microRNA (miR) have important and diverse roles in the proliferation, apoptosis and metastasis of human cancer cells. In the present study, the molecular regulation mechanism of miR-30a and its potential target, Myb-related protein B (MYBL2) was investigated in NSCLC. Reverse transcription-quantitative polymerase chain reaction results showed that miR-30a was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…MYBL2 and TFDP1 are targeted by five common miRNAs (hsa-miR-30a-5p, hsa-miR-30b-5p, hsa-miR-30c-5p, hsa-miR-30d-5p, hsa-miR-30e-5p), though they belong from same miRNA family. A previous study showed the down-regulation of hsa-miR-30a-5p which directly targeting MYBL2 mRNA in NSCLC (93). Interestingly, TCGA NSCLC dataset showed higher mutation rates in the genes of “driver-network” as well as its upstream regulators FOXM1 and MYBL1 in the NSCLC (Figure 6).…”
Section: Discussionmentioning
confidence: 97%
“…MYBL2 and TFDP1 are targeted by five common miRNAs (hsa-miR-30a-5p, hsa-miR-30b-5p, hsa-miR-30c-5p, hsa-miR-30d-5p, hsa-miR-30e-5p), though they belong from same miRNA family. A previous study showed the down-regulation of hsa-miR-30a-5p which directly targeting MYBL2 mRNA in NSCLC (93). Interestingly, TCGA NSCLC dataset showed higher mutation rates in the genes of “driver-network” as well as its upstream regulators FOXM1 and MYBL1 in the NSCLC (Figure 6).…”
Section: Discussionmentioning
confidence: 97%
“…In this study, we showed that miR‐30a is involved in the proliferation of AI cells by targeting MYBL2, FOXD1, and SOX4, and the schematic diagram was shown in Figure 6F. MYBL2 previously had been reported as miR‐30a target in acute myeloid leukemia 42 and non–small‐cell lung cancer 43 . FOXD1 was also a miR‐30a target in human ovarian carcinoma 44 and osteosarcoma 45 .…”
Section: Discussionmentioning
confidence: 62%
“…Studies have also showed that miR-30a induces cell cycle arrest. Overexpression of miR-30a increases cell apoptosis and induces cell cycle arrest in non-small cell lung cancer (38). miR-30a has also been demonstrated to promote cell cycle arrest at the G1 phase (39).…”
Section: Discussionmentioning
confidence: 99%